P103 Cardiopulmonary Exercise Testing In COPD: Cycle Ergometry or Treadmill Which is Better?. (19th November 2012) - Ali, Mir Shad; Joshi, S; Singh, Mandeep; Sandhya, AS; Talwar, D
Abstract : Introduction/Objectives: Traditionally Cycle Ergometry is used for CPET to assess functional exercise capacity in COPD. However, walking is closely related to daily functional needs of COPD patients. The aim of this study was to evaluate the efficacy and tolerance of Naughton's treadmill protocol over Cycle Ergometry in COPD patients during maximal CPET. Result: All patients were able to complete the treadmill protocol in CPET, while on the Cycle Ergometry test it was symptom limited. The mean age was 58.0 + 10.1 years with mean FEV1% of 56.11+ 26.2%. VE, HR, VE/VCO2, VE/VO2, VD/VT and PETCO2 at the end of the exercise during treadmill and Cycle Ergometry were not statistically different. Hence all variables e.g. VO2 peak, VO2% predicted, duration of exercise and VO2 at LT were comparable. The VO2 Peak during treadmill was significantly higher during treadmill as compared to Cycle Ergometry (1347.5+308 ml/min vs. 1089.9+277.9 ml/min respectively; p=0.013). The duration of exercise was also significantly more during treadmill as compared to cycle ergometer (12.6+3.8 min. vs. 8.3+3.12 min. respectively p=0.002; p=0.68) although there was no significant difference in VO2 at LT (41.3 + 14.1% during treadmill vs. 33.4 + 10.6% during cycle ergometry; p-value- 0.087). Conclusion: Patients performing CPET on treadmill as compared to Cycle Ergometry showed increase exercise capacity. Hence in Indian COPD subjects treadmill CPET may be better for functional assessment.